Retorika Storyteller Semarang Walking Tour Dalam Membangun Narasi Bagi Wisatawan - Aji, Iqfarchan Visnu; Mukaromah, Mukaromah (Jurnal Pustaka Komunikasi, 2025)
This research is motivated by a tour guide (storyteller) in the process of telling a message about a type of tourist destination. Semarang is a city  improving its tourist destination by highlighting the slogan variety of culture. This gives Semarang several reference destinations such as cultural tourism in the Chinatown area, nature tourism in the urban forest, and special culinary interest tourism. This research aims to determine the rhetorical process of story messages conveyed by storytellers to tourists. The research uses a qualitative approach with case study methods, and collection techniques by observing walking tour activities and interviews with storytellers (tour guides). The research results show that the narrative process related to walking tourist routes based on types of tourist interest according to the Directorate General of the Government of the Republic of Indonesia involves creating a route story, taking into account 3 rhetorical evidence including credibility, emotional approach, and logic then going through the creation process by organizing the message. To impress tourists, storytellers use style in language and coordinate with gestures, expressions, and voice intonation, efforts are made to memorize the material so that the story can be conveyed optimally.